The Fictionalist’s Attitude Problem - Oddie, Graham (Ethical theory and moral practice, 2007)
According to John Mackie, moral talk is representational (the realists go that bit right) but its metaphysical presuppositions are wildly implausible (the non-cognitivists got that bit right). This is the basis of Mackie’s now famous error theory: that moral judgments are cognitively meaningful but systematically false. Of course, Mackie went on to recommend various substantive moral judgments, and, in the light of his error theory, that has seemed odd to a lot of folk. Richard Joyce has argued that Mackie’s approach can be vindicated by a fictionalist account of moral discourse. And Mark Kalderon has argued that moral fictionalism is attractive quite independently of Mackie’s error-theory. Kalderon argues that the Frege–Geach problem shows that we need moral propositions, but that a fictionalist can and should embrace propositional content together with a non-cognitivist account of acceptance of a moral proposition. Indeed, it is clear that any fictionalist is going to have to postulate more than one kind of acceptance attitude. We argue that this double-approach to acceptance generates a new problem – a descendent of Frege–Geach – which we call the acceptance–transfer problem. Although we develop the problem in the context of Kalderon’s version of non-cognitivist fictionalism, we show that it is not the non-cognitivist aspect of Kalderon’s account that generates the problem. A closely related problem surfaces for the more typical variants of fictionalism according to which accepting a moral proposition is believing some closely related non-moral proposition. Fictionalists of both stripes thus have an attitude problem.